Optimal selection of aerobic biological treatment for a petroleum refinery plant - Orbecido, Aileen H. (Animo Repository, 2016)
© 2016, AIDIC Servizi S.r.l. Aerobic biological treatment has been known to be an integral part of a typical wastewater treatment plant that reduces the pollution load of wastewater from either municipality or industry having soluble organic contaminants. For example, the conventional activated sludge process has been widely used in a long time but a variety of biological treatment systems were also being considered in recent years to meet a more stringent discharge standards. In designing such wastewater treatment plant, several criteria have to be taken into account that includes the technical, socio-economic and environmental aspects of the decision problem. This work thus applies a multiple criteria analysis based on Group Fuzzy AHP for optimal selection of the different aerobic biological treatment technologies. This technique decomposes the decision problem into a hierarchic structure and derives priority weights for the ranking of the alternatives. The decision model also incorporates the ambiguity-type uncertainty when eliciting pairwise comparison judgment from a domain expert. A case study applied to a petroleum refinery plant is presented considering the following alternatives: 1) conventional activated sludge system (CAS); 2) sequencing batch reactor (SBR); 3) integrated fixed film activated sludge system (IFAS); and 4) membrane bioreactor (MBR). These wastewater treatment systems were then evaluated and compared with respect to the following criteria: 1) economic sub-criteria such as the capital and operating cost; 2) environmental sub-criteria such as the treated effluent quality, ability to adjust to hydraulic and pollutant loading, ability to cope with oil ingress, and land footprint; 3) technical sub-criteria such as pre-treatment and secondary clarifier requirement, reliability and validity of technology, and complexity to operate and control. The Group Fuzzy AHP model showed that SBR is the most preferred option followed by CAS as regard to aerobic biological system for the treatment of petroleum refinery wastewater. Indications suggest from sensitivity analysis that the ranking of the alternatives is influenced largely by the weighting of economic and environmental aspects.